Echocardiographic Results of Transcatheter Versus Surgical Aortic Valve Replacement in Low-Risk Patients: The PARTNER 3 Trial. Issue 19 (12th May 2020) - Pibarot, Philippe; Salaun, Erwan; Dahou, Abdellaziz; Avenatti, Eleonora; Guzzetti, Ezequiel; Annabi, Mohamed-Salah; Toubal, Oumhani; Bernier, Mathieu; Beaudoin, Jonathan; Ong, Géraldine; Ternacle, Julien; Krapf, Laura; et al.
Abstract : Background: This study aimed to compare echocardiographic findings in low-risk patients with severe aortic stenosis after surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR). Methods: The PARTNER 3 trial (Placement of Aortic Transcatheter Valves) randomized 1000 patients with severe aortic stenosis and low surgical risk to undergo either transfemoral TAVR with the balloon-expandable SAPIEN 3 valve or SAVR. Transthoracic echocardiograms obtained at baseline and at 30 days and 1 year after the procedure were analyzed by a consortium of 2 echocardiography core laboratories. Results: The percentage of moderate or severe aortic regurgitation (AR) was low and not statistically different between the TAVR and SAVR groups at 30 days (0.8% versus 0.2%; P =0.38). Mild AR was more frequent after TAVR than SAVR at 30 days (28.8% versus 4.2%; P <0.001). At 1 year, mean transvalvular gradient (13.7±5.6 versus 11.6±5.0 mm Hg; P =0.12) and aortic valve area (1.72±0.37 versus 1.76±0.42 cm 2 ; P =0.12) were similar in TAVR and SAVR. The percentage of severe prosthesis–patient mismatch at 30 days was low and similar between TAVR and SAVR (4.6 versus 6.3%; P =0.30). Valvulo-arterial impedance (Zva ), which reflects total left ventricular hemodynamic burden, was lower with TAVR than SAVR at 1 year (3.7±0.8 versus 3.9±0.9 mm Hg/mL/m 2 ; P <0.001). Tricuspid annulus plane systolic excursion decreased and the percentage of moderate or severe tricuspid regurgitation increased from baseline to 1 year in SAVR but remained unchanged in TAVR. Irrespective of treatment arm, high Zva and low tricuspid annulus plane systolic excursion, but not moderate to severe AR or severe prosthesis–patient mismatch, were associated with increased risk of the composite end point of mortality, stroke, and rehospitalization at 1 year. Conclusions: In patients with severe aortic stenosis and low surgical risk, TAVR with the SAPIEN 3 valve was associated with similar percentage of moderate or severe AR compared with SAVR but higher percentage of mild AR. Transprosthetic gradients, valve areas, percentage of severe prosthesis–patient mismatch, and left ventricular mass regression were similar in TAVR and SAVR. SAVR was associated with significant deterioration of right ventricular systolic function and greater tricuspid regurgitation, which persisted at 1 year. High Zva and low tricuspid annulus plane systolic excursion were associated with worse outcome at 1 year whereas AR and severe prosthesis–patient mismatch were not. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02675114. Abstract : Supplemental Digital Content is available in the text.